MiR-223 or miR-126 predicts resistance to dual antiplatelet therapy in patients with ST-elevation myocardial infarction. Issue 6 (June 2021) - Li, Xiaojing; Yao, Qi; Cui, Hanbin; Yang, Jun; Wu, Nan; Liu, Yahui; Zhou, Ying; Zhang, Yinwei; Su, Jia; Xia, Yezi; Chen, Xiaomin
Objective: To explore the role of miR-223 and miR-126 in predicting treatment responses to dual antiplatelet therapy (DAPT) in patients with ST-elevation myocardial infarction (STEMI). Methods: Plasma miR-223 and miR-126 levels were measured before treatment. Treatment responses and 2-year survival were determined. In vitro experiments were performed to explore the mechanism of action. Results: Patients with resistance to DAPT had a lower level of miR-223 and miR-126. Cardiac-event-free survival was shorter in patients with lower miR-223 or miR-126 levels. MiR-223 and miR-126 independently predicted DAPT resistance. Modulating miR-223 or miR-126 in platelets in vitro significantly changed the response to clopidogrel by regulating platelet aggregation. Conclusion: MiR-223 and miR-126 play a role in DAPT resistance and may provide potential biomarkers in patients with STEMI.